Predictors of Altmetric Score in Top-Cited Orthopaedic Articles: A Bibliometric Analysis - Muhammad Talal Ibrahim; Haider Sheraz; Muhammad Hamza Shuja; Hamza Imran; Anum Ali; Shahryar Noordin (Journal of the Pakistan Medical Association, 2026)
Research articles are increasingly being disseminated on social media, which is not captured by traditional bibliometrics. The Article-Level Metric score captures the ‘social’ impact of such research articles as well. The current bibliometric analysis was planned to identify predictors of high Altmetric score in the top-cited articles related to orthopaedic surgery. Multilevel, mixedmethod, linear regression was employed to adjust for clustering of article-level and journal-level factors among 810 articles from 27 journals. The study was conducted at Aga Khan University, Karachi, Pakistan from June to December 2023. In multivariable, multilevel, linear regression, each additional citation led to a 0.33-unit increase in Article-Level Metric score (beta=0.33, p=0.02), articles published in the Netherlands had a higher score by 10.6 units compared to Germany (beta=10.60, p=0.01), and each additional unit increase in journal’s impact factor increased the score by 1.73 units (beta=1.73, p=0.04) Keywords: Bibliometrics, Altmetric, Twitter, Social media, Research.